The Effectiveness of Game-Based Flipped Learning on Academic Achievement and Engagement - Austin Gautier; Mara Alagic (The Advocate, 2025)
Abstract This study aimed to determine if a game-based flipped learning (GBFL) environment was an effective learning model relative to flipped learning alone. Three sections of 6th-grade science students received varied methods of instruction by the same teacher over four weeks. One section received traditional, face-to-face instruction, another section worked in a flipped learning (FL) environment, and the last section worked in a proposed GBFL environment. A standardized pretest and posttest alongside a mixed-method student survey were administered to determine the effectiveness of each strategy in terms of academic achievement, student engagement, and satisfaction. The study's results indicated that GBFL resulted in similar academic improvements yet greater student satisfaction than the other two groups. ANOVA and Pearson Product Moment Analyses indicated that each learning method resulted in substantial academic improvement with slight variance between groups (p=0.07). A moderate positive correlation existed between posttest scores and student satisfaction in the GBFL group (r=0.314). These results indicate the potential of GBFL as a learning model and the future research required for validation.
Keywords: Gamified learning; Flipped Learning; Game based learning; game; educational games; instructional games